Chaperonin TRiC/CCT Participates in Mammarenavirus Multiplication in Human Cells via Interaction with the Viral Nucleoprotein - Sakabe, Saori; Witwit, Haydar; Khafaji, Roaa; Cubitt, Beatrice; de la Torre, Juan C. (Journal of virology, 2023)
Host-directed antivirals have gained great interest as an antiviral strategy to counteract the rapid emergence of drug-resistant viruses. The chaperonin TRiC/CCT complex has been involved in the life cycle of several viruses, including dengue, Zika, and influenza viruses. The eukaryotic chaperonin containing tailless complex polypeptide 1 ring complex (CCT, also known as TCP-1 Ring Complex, TRiC/CCT) participates in the folding of 5% to 10% of the cellular proteome and has been involved in the life cycle of several viruses, including dengue, Zika, and influenza viruses, but the mechanisms by which the TRiC/CCT complex contributes to virus multiplication remain poorly understood. Here, we document that the nucleoprotein (NP) of the mammarenavirus lymphocytic choriomeningitis virus (LCMV) is a substrate of the human TRiC/CCT complex, and that pharmacological inhibition of TRiC/CCT complex function, or RNAi-mediated knockdown of TRiC/CCT complex subunits, inhibited LCMV multiplication in human cells. We obtained evidence that the TRiC/CCT complex is required for the production of NP-containing virus-like particles (VLPs), and the activity of the virus ribonucleoprotein (vRNP) responsible for directing replication and transcription of the viral genome. Pharmacological inhibition of the TRIC/CCT complex also restricted multiplication of the live-attenuated vaccine candidates Candid#1 and ML29 of the hemorrhagic fever causing Junin (JUNV) and Lassa (LASV) mammarenaviruses, respectively. Our findings indicate that the TRiC/CCT complex is required for mammarenavirus multiplication and is an attractive candidate for the development of host directed antivirals against human-pathogenic mammarenaviruses. IMPORTANCE Host-directed antivirals have gained great interest as an antiviral strategy to counteract the rapid emergence of drug-resistant viruses. The chaperonin TRiC/CCT complex has been involved in the life cycle of several viruses, including dengue, Zika, and influenza viruses. Here, we have provided evidence that the chaperonin TRiC/CCT complex participates in mammarenavirus infection via its interaction with the viral NP. Importantly, pharmacological inhibition of TRiC/CCT function significantly inhibited multiplication of LCMV and the distantly related mammarenavirus JUNV in human cells. Our findings support that the TRiC/CCT complex is required for multiplication of mammarenaviruses and that the TRiC/CCT complex is an attractive host target for the development of antivirals against human-pathogenic mammarenaviruses.